Risk Management Maturity in Construction Service Companies on Time Performance and Road Construction Quality - Abdul Hamid Payapo; Nurmaiyasa Marsaoly; Abdul Gaus (Indonesian Journal of Multidisciplinary Science, 2023)
The risks that have the most influential impact during the construction work of the Sp. Dodinga-Sofifi-Akelamo-Payahe-Weda Road Preservation project in North Maluku Province, are the work environment (the surrounding conditions of the road  (right and left) which are overgrown with wild plants, so that it looks like the road feels poorly maintained),  equipment (inadequate opererators in operating heavy equipment during the implementation of work), materials (There is often a shortage of materials (non-local) because they have to be brought in from outside the area), methods of carrying out work (Implementation of work not in accordance with predetermined specifications), human resources, (Human resources who work cannot coordinate properly and do not produce road projects that  well), financial (Insufficient financial capability of the contractor and use of unused contract advances for the purposes of project implementation), and design changes (Frequent design changes by the owner due to use or function that changed from the initial planning while the work was being carried out).